2022
DOI: 10.1039/d2sc02939a
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of ion-electrode interactions of linear polyimides and alkali metal ions for next generation alternative-ion batteries

Abstract: Organic electrode materials offer unique opportunities to utilize ion-electrode interactions to develop diverse, versatile, and high-performing secondary batteries, particularly for applications requiring high power densities. However, a lack of well-defined...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(50 citation statements)
references
References 71 publications
0
50
0
Order By: Relevance
“…Decreasing the charge density (i.e., increasing the size) of the monovalent cation from Li + to n Bu 4 N + resulted in a decrease in the magnitude of the second reduction potential, from 2.031 V (Li + ) to 1.899 V (Na + ) to 1.740 V (K + ) and 1.773 V ( n Bu 4 N + ) vs Li/Li + , respectively (SI Table S13, see Section S12 for further discussion on n Bu 4 N + ). This finding suggests that among monovalent cations, Li + best stabilizes the doubly reduced form of poly­(BTDA)-EG due to the hard–hard match of the reduced carbonyl units and the Li + cations. , …”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Decreasing the charge density (i.e., increasing the size) of the monovalent cation from Li + to n Bu 4 N + resulted in a decrease in the magnitude of the second reduction potential, from 2.031 V (Li + ) to 1.899 V (Na + ) to 1.740 V (K + ) and 1.773 V ( n Bu 4 N + ) vs Li/Li + , respectively (SI Table S13, see Section S12 for further discussion on n Bu 4 N + ). This finding suggests that among monovalent cations, Li + best stabilizes the doubly reduced form of poly­(BTDA)-EG due to the hard–hard match of the reduced carbonyl units and the Li + cations. , …”
Section: Resultsmentioning
confidence: 91%
“…One of the most exciting features of organic electrode materials is that they can be readily adapted to work with almost any cation, including those such as Na + and Mg 2+ that are more abundant than Li + , and their redox properties can be optimized by tuning hard–soft acid–base interactions. Indeed, previous molecular studies have demonstrated that 1,2-diones are promising potential electrode materials for Mg-ion batteries because the two one-electron waves observed with monovalent cations such as Li + collapse into a single two-electron reduction wave with Mg 2+ cations due to the excellent hard–hard match of the divalent cation and the reduced carbonyl groups . However, this promising feature has not been demonstrated in polymeric electrode materials to date.…”
Section: Resultsmentioning
confidence: 99%
“…This finding suggests that among monovalent cations, Li + best stabilizes the doubly reduced form of poly(BTDA)-EG due to the hard-hard match of the reduced carbonyl units and the Li + cations. 29,[68][69][70] Intriguingly, switching from monovalent cations to divalent Mg 2+ caused the second reduction peak to dramatically shift to 2.501 V vs. Li/Li + , leading the second reduction peak to almost merge with the first peak to reveal a nearly simultaneous twoelectron transfer (Figure 8c). This finding suggests that Mg 2+ best stabilizes doubly reduced poly(BTDA)-EG.…”
Section: Resultsmentioning
confidence: 97%
“…One of the most exciting features of organic electrode materials is that they can be readily adapted to work with almost any cation, including those such as Na + and Mg 2+ that are more abundant than Li + , [65][66][67] and their redox properties can be optimized by tuning hard-soft acid-base interactions. [68][69][70] Indeed, previous molecular studies have demonstrated that 1,2-diones are promising potential electrode materials for Mg-ion batteries, because the two one-electron waves observed with monovalent cations such as Li + collapse into a single two-electron reduction wave with Mg 2+ cations due to the excellent hard-hard match of the divalent cation and the reduced carbonyl groups. 29 However, this promising feature has not been demonstrated in polymeric electrode materials to date.…”
Section: Resultsmentioning
confidence: 99%
“…Lithium-ion batteries (LIBs) have been widely used in the elds of new-energy electric vehicles, portable electronic devices, and short to mid-term stationary energy storage, occupying a great share in the highly competitive battery market. [1][2][3][4] A conventional lithium-ion battery typically consists of a modied carbon-based anode and a lithium transition metal oxide-based cathode. [5][6][7] In the face of rapid developments in science and technology, these traditional LIB electrode materials are increasingly unable to meet the demanding requirements for capacity, energy density, safety, size and cost.…”
Section: Introductionmentioning
confidence: 99%